2009
DOI: 10.1111/j.1442-2018.2009.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of a modified fall assessment tool in nursing homes: Experience from Slovenia

Abstract: The aim of the study was to evaluate the predictive validity of the Modified Fall Assessment Tool (MFAT) in a nursing home setting. The study involved 83 residents from a nursing home in Slovenia with an average age of 81 years. To determine the predictive characteristics of the MFAT, a receiver operating characteristic curve analysis was applied. During the observation period of 12 weeks, 18 residents fell. The fallers had a significantly higher history of falls, a higher number of diagnoses, more medication,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
(59 reference statements)
0
7
0
2
Order By: Relevance
“…A further four cohort studies found fallers had a higher BMI than non‐fallers or that a higher BMI was associated with falls 34–37 . A further 11 studies found no difference in BMI between fallers and non‐fallers 19–21,23,25,27–32 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further four cohort studies found fallers had a higher BMI than non‐fallers or that a higher BMI was associated with falls 34–37 . A further 11 studies found no difference in BMI between fallers and non‐fallers 19–21,23,25,27–32 …”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies measured BMI in fallers 11,12,18–21,23–25,27–37 . These included three descriptive studies, one case control study and 16 cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Questionnaires filled out by (i) clinical staff [41][42][43][44][45], (ii) the subjects themselves [46,47], or (iii) by telephone interviews [48] represent one of the most prevalent approaches for fall risk assessment in the clinic. While questionnaires can reach out to large cohorts in an efficient manner, a number of limitations are associated with this form of data collection; for questionnaires filled out by employees, well-trained staff are required in order to avoid bias; self-reported questionnaires can only measure explicit knowledge and this knowledgeespecially in the elderly-is often not an objective reflection of the truth [6].…”
Section: Deficits In Common Testsmentioning
confidence: 99%
“…노인에게 낙상이 발생될 것을 예방하기 위해 여러 가지 전략 을 사용한다 (Kato et al, 2008;Ryu, Roche, & Brunton, 2009) (Hong, 2011;Hook, 2007;Jakovljevic, 2009;Kim, Lee, & Ham, 2009;Lim et al, 2010;Menant et al, 2008;Sung et al, 2006;Tromp et al, 2001). …”
Section: 병원이나 요양기관에서 의료인을 포함한 건강관리자들은unclassified